PENGARUH MARKETING PUBLIC RELATION TERHADAP LOYALITAS PELANGGAN PADA PT. JALUR NUGRAHA EKAKURIR (JNE) BANDUNG - Hidayat, Taufiq (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
The purpose of this study to determine the relationship and influence of Marketing and Public Relations on customer loyalty JNE Bandung branch. The method used is quantitative research methods. The model study was conducted by the method of explanation or correlation method. The number of respondents 45 people with random sampling techniques. The coefficient of determination of the role of marketing public relations to customer loyalty 56.55% showed marked positive correlation coefficients that describe the direction of positive effects as well, by the better Marketing Public Relations (X) is carried out, then the effect on customer loyalty (Y) which formed. The coefficient of determination of the role of marketing public relations to customer loyalty is equal to 0.5655. The value of 56.55% indicates that customer loyalty is influenced by the role of Marketing and Public Relations, while the remaining 43.45% is determined by other factors outside of the study. Keywords: marketing public relations; customer loyalty.